ANALISIS DESKRIPTIF KUALITATIF IMPLEMENTASI WORD OF MOUTH DALAM KOMUNIKASI PEMASARAN PRODUK BROOKLAND COFFEE - Fachreza, Abdullah Vicky Imam; Soebiagdo, Soebiagdo (Transpublika Publisher, 2024)
This research aims to explore and describe exactly how the application of word of mouth marketing communication in Brookland Coffee's product marketing strategy. The research method uses a descriptive qualitative approach by conducting direct observations and in-depth interviews with key informants consisting of the owner, baristas, and consumers of Brookland Coffee. The results showed that Brookland Coffee consistently implements a word of mouth strategy by prioritizing aspects of trust and consumer confidence. This strategy is implemented through a family approach, networking, and community building, especially the bicycle community. The research conclusion revealed that the effectiveness of word of mouth succeeded in strengthening Brookland Coffee's marketing communications, supported by consistent product quality, good service (hospitality), and the use of Instagram social media as a supporting platform for marketing strategies. Brookland Coffee succeeded in building a strong brand identity through a combination of offline and online word of mouth communication.